2013
DOI: 10.1177/1352458513494491
|View full text |Cite
|
Sign up to set email alerts
|

Interferon beta-1b reduces black holes in a randomised trial of clinically isolated syndrome

Abstract: NCT00544037.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 30 publications
(73 reference statements)
0
24
1
Order By: Relevance
“…24,25 In addition to contrast enhancing and active T2 lesions to measure acute MS related inflammation, several MRI markers of focal neurodegeneration should be considered, such as chronic T1 hypointense lesions ('black holes') that persist longer than 6 months. [26][27][28][29] This imaging finding may hold promise for predicting disability progression and monitoring remyelination, and represents a possible new outcome marker for MS therapies. 30,31 Global brain volume changes The pathological hallmark of MS is the presence of multi ple focal demyelinating lesions in the cerebral white and grey matter, but substantial brain atrophy can also occur.…”
Section: Focal Lesionsmentioning
confidence: 99%
“…24,25 In addition to contrast enhancing and active T2 lesions to measure acute MS related inflammation, several MRI markers of focal neurodegeneration should be considered, such as chronic T1 hypointense lesions ('black holes') that persist longer than 6 months. [26][27][28][29] This imaging finding may hold promise for predicting disability progression and monitoring remyelination, and represents a possible new outcome marker for MS therapies. 30,31 Global brain volume changes The pathological hallmark of MS is the presence of multi ple focal demyelinating lesions in the cerebral white and grey matter, but substantial brain atrophy can also occur.…”
Section: Focal Lesionsmentioning
confidence: 99%
“…Conventional MRI techniques are of limited value in monitoring remyelination. However, the measurement of the evolution of transient T1 hypointense lesions (black holes, BH) as a potential marker is a well-established concept and is increasingly being applied in clinical treatment trials [45]. However, there is broad spectrum of advanced imaging techniques available allowing a more specific in vivo evaluation of the myelin content.…”
Section: Resultsmentioning
confidence: 99%
“…Placebo‐controlled studies have shown that, over a 6‐12 month period, approximately 25‐40% of active MS lesions will evolve into T1H lesions 6, 79, 10, 11, 12 …”
Section: Introductionmentioning
confidence: 99%